Arteriovenous fistula cannulation in hemodialysis: A vascular access clinical practice guidelines narrative review. Issue 5 (September 2022) - Pinto, Rui; Sousa, Clemente; Salgueiro, Anabela; Fernandes, Isabel
The cannulation of an arteriovenous fistula (AVF) by the hemodialysis (HD) nurse is challenging. Despite it being the focus of extensive research, it is still one of the majors causes of damage making it prone to failure. A considerable number of Clinical Practice Guidelines (CPGs) for the management of vascular access (VA) have been published worldwide over the past two decades. This review aimed to assess all information available in the selected CPG regarding AVF cannulation for HD providing a comprehensive analysis in order to interpret possible future cannulation approaches. A total of seven CPGs were described in a coding table separated in seven subthemes: Initiation of cannulation, preparation, technique, needle selection, surveillance, pain, and education. Our analysis outlines current CPGs for HD VA cannulation with lack of good evidence support for the majority of the recommendations, showing that, there is an urgent need for international collaboration and coordination to ensure relevant and high-quality evidence. Future CPGs must consider recommendations with better grading of evidence aiming patient-centered care and nurse decision models that can potentially represent better AVF cannulation outcomes.